Genetic identity of Tor malabaricus(Jerdon)(Teleosti:Cyprinidae) as revealed by RAPD markers - Silas, E G; Gopalakrishnan, A; John, Lijo; Shaji, C P (Indian Journal of Fisheries, 2011)
Tor malabaricus is a mahseer species endemic to the Western Ghats.